Re-imagining Egyptian national identity in the post-Arab Spring novel: the stylistics of representing social agents and building fictional worlds in The Queue and Otared - Mohamed, Nourhan (2021)
This thesis examines the stylistic construction of national identity in two translated critically acclaimed works of post-Arab Spring Egyptian prose fiction: The Queue (2016) by Basma Abdel Aziz, and Otared (2016) by Mohammed Rabie. Using Bourdieu's (1977) Theory of Practice and Anderson's (2006) Imagined Communities, two parallel conceptualizations of national identity in fiction are put forth. The first is that of deliberate action, habitual practice, or interactional processes by individual social agents, investigated on the clause level through the lens of Systemic Functional Grammar (SFG); the second is that of narrative technique or fictional world-building, examined through Text-World Theory (TWT). The clause-level representation of social agents is contextualized into a discussion of symbolic power in Egyptian fields of practice before and after the Arab Spring, while fictional world-building techniques are compared with previous works of post-revolutionary Egyptian fiction in terms of narration/focalization, spatiality and temporality, schema activation, and the overall narrative genre of the texts.